CONNECTION SUPPORT FAMILY AND EDUCATION LEVEL WITH POST STROKE DEPRESSION (PSD) IN STROKE PATIENTS - Mufidah, Nisfil; Wahyudi, Rahmad; Priyanto, Agus; Nur, Nova Adila (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2024)
Stroke is the main cause of death globally and the main cause of disability with an increasing incidence in developing countries . Stroke is divided into two types, namely ischemic stroke and hemorrhagic stroke. Stroke can cause disturbances in areas of the brain that function as neurobehavior , which can cause psychiatric symptoms such as post-stroke depression. Depression occurs as a result of one of the complications after experiencing a stroke (post-stroke) and is associated with decreased healing function, activity or social support and cognitive function . Meanwhile, Post Stroke Depression (PSD) is a post-stroke neuropsychiatric complication that most often occurs in around half of all stroke patients. Several hypotheses are involved in the incidence of PSD, namely psychosocial vulnerability and biological determination . The aim of the research is to find out i There is connection support family and level education with post stroke depression in stroke patients.This use cross-sectional . Amount population as many as 94 stroke patients with sample of 76 respondents , with technique purposive sampling. Instruments used is questionnaire support family and HDRS. Test statistics use correlation test spermank rank with a 0.05. Researcher suggestions expected can increase understanding about stroke, increase draft self so that spared from depression